A Study to Assess the Effectiveness of Acute Coronary Syndrome Algorithm on Nursing Management of Patient with Acute Coronary Syndrome among Staff Nurse of Selected Hospital Waghodia. - H.N., Ravindra; Prajapat, Manish; Balagavi, Dayanand (International Journal of Nursing Education)
Background: In the Asia for more than 4.2 billion populations is suffer with the ACS. Acute coronary syndrome (ACS) is now a major cause of death in the hospital the mortality is more than 5%.[1] So it is important to enhance the knowledge and practice regarding ACS algorithm among staff nurses. Method: Qualitative research approach with pre- experimental one group pre-test and post-test design with non-probability convenience sampling was used to collect the 70 samples. A structured knowledge questionnaires and Practice checklist was prepared to assess the knowledge and practice of staff nurses. Result: With regards to the pre-test assessment the score of 24(34%) subject was having moderate level of knowledge and 46(66%) subjects were having inadequate knowledge while in post-test 5(7%) of subject having moderate level of knowledge and 65(93%) subject having adequate level of knowledge The obtained pre-test mean score was 7.14 and post- test mean score was 15.24 the mean difference of the pre-test and post- test is 8.10 which shows the improvement in the level of knowledge among subjects, The pre-test SD was 1.35 and post- test SD 1.33 The obtained pair "t" test value 33.270, df=69 significant at 0.05 level. Whereas the pre-test score of practice shows 23(32.85%) subjects had inadequate practice and 47(67.14%) subjects had moderate practice, the post test data revels that 24(34.28%) subjects were had moderate practice and 46(65.71%) subjects had adequate practice towards ACS. The obtained pair "t" test value 27.790, df=69 shows significant at 0.05 level. It indicates that there was increased in the level of knowledge and improves practice towards acute coronary syndrome after providing nursing care algorithm. So that H1 research hypothesis accepted. The pre-test practice score had not significant association all demographic variable so H2 research hypothesis was rejected. Conclusion: The findings of the study concluded that majority of subjects had inadequate level of knowledge and adequate practice. The nursing care ACS algorithm was effective among staff nurses in improving knowledge (t (69) = 33.270) and practice (t (69) = 27.790) significant at 0.05 level regarding acute coronary syndrome.